Identifying effective mechanisms for marketing integration process to Malaysian acquirers - Jedin, Mohd. Haniff; Md. Saad, Norsafinas (2011)
Marketing integration in mergers and acquisitions (M&As) is an important avenue in ensuring the survival of the combined firms. This can be achieved by compressing and redeploying all marketing resources from both sides; the acquirer and acquired firm. Perhaps, marketing integration is a backbone of firm combination due to its nature which potentially to generate higher revenue of the newly-combined firm. Yet, the existing study does not clearly investigate mechanisms that contribute to the marketing integration process in cross-border M&As. The purpose of this study is to explore the effective mechanisms that can improve the marketing integration process in cross-border M&As. Thus, marketers' collaboration, interaction, marketing synergy and redeployment of marketing resources were propose as key mechanisms in marketing integration process in cross-border M&As. Result indicates that marketing synergy and redeployment of marketing resources have strong significant impact towards the extent of integration. Meanwhile, there is a striking result pertaining to the relationships between interaction and the speed of integration which is significantly important but negatively influenced.